Argonaute-3 activates the let-7a passenger strand microRNA - Winter, Julia; Diederichs, Sven (RNA biology, 2013)
MicroRNA duplices are separated into a guide and a passenger strand. By convention, the guide represents the active microRNA while the passenger is supposedly degraded. However, passenger strands also emerge as active microRNAs. It is unknown whether the guide-to-passenger-strand ratio can be actively regulated and which factors influence strand incorporation into the RISC. Here, we identify a microRNA with a variable guide-to-passenger-strand ratio along with its regulatory factor: Human Argonaute-3 specifically enhances the passenger strand expression and activity of the tumor suppressor microRNA let-7a. This post-maturational effect is mediated by the Ago3 PAZ and MID domains yielding an elevated affinity for let-7a-3p. Notably, this is independent of the 5′-terminal basepair stability, challenging the universality of the respective rule for microRNA strand selection. Thus, this study uncovers the first protein regulator of the ratio between microRNA guide and passenger strand expression and activity.